(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dual inverter fed IM drive is commonly employed in EV applications. In this application, SVPWM based PWM generator was utilised. However, they produce a high common-mode voltage(CMV). Because of this, bearing of motor will be affected and in turn, results in EMI problems. Hence, to overcome this problem, this work introduced a novel PWM generation techniques named scalar coupled and decoupled PWM topology to control a three-level symmetrical DI fed OEWIM. Hence, to find out the effectiveness of the proposed topologies, its operation is examined under both continuous and discontinuous modes of operation using MATLAB simulation. From the acquired results, it is concluded that this coupled PWM topology topology exhibits reduced CMV and harmonics when compared to decoupled topology